Assessing fall risk in osteoporosis patients: a comparative study of age-matched fallers and nonfallers - Moon, Seong Hyun; Doshi, Krupa B.; Lockhart, Thurmon (Frontiers in Digital Health, 2024)
This study aimed to investigate sway parameters and physical activity level of the age/gendermatched older adults with osteoporosis faller and nonfaller patients. By examining these factors, our objective was to understand how these faller and nonfaller groups with osteoporosis differed particularly in terms of balance capabilities and their impact on physical activity levels. We recruited 24 patients with osteoporosis: 12 who reported a fall within a year before recruitment (fallers) and 12 without falls (nonfallers). Given the close association between biochemical markers of musculoskeletal health such as serum calcium, parathyroid hormone (PTH), Vitamin D, and renal function, we compared these markers in both groups. As a result, elderly individuals with osteoporosis and with a history of falls within the preceding year indicated significantly higher sway velocity (P = 0.012*), sway area (P < 0.001*), and sway path length (P = 0.012*). Furthermore, fallers had significantly lower calcium (P = 0.02*) and Parathyroid hormone (PTH) (P = 0.02*), as well as higher Alkaline Phosphatase (ALP) (P = 0.02*) as compared to nonfallers despite similar vitamin D and creatinine levels. In conclusion, diminished biochemical factors in the osteoporosis faller group could possibly cause postural instability resulting in lower physical activity levels in the osteoporosis fall group and increasing the risk of falls.